Experimental Study on Physical and Dynamic Mechanical Properties of Temperature-Water Coupled Sandstone. (3rd August 2021) - Ping, Qi; Qi, Dezhi; Diao, Qi; Zhang, Chuanliang; Gao, Qi; Wu, Yulin
Abstract : In order to study the influence characteristics of water bath at different temperatures on rock physical and dynamic mechanical properties, a total of 15 groups of temperature-water bath treatment were carried out on coal mine roadway sandstone at 25°C∼95°C, and the basic physical parameters were tested. The impact compression test was carried out using the split Hopkinson pressure bar (SHPB) device. The results show that, with the increase of water bath temperature, the particle gap on the specimen surface increases. The volume, mass, and density of the specimens all increased with the increase of water bath temperature, and the increase was closely related to the water bath temperature. The dynamic compressive strength increases as a quadratic function of the water bath temperature, and the rate of increase is different before and after 45°C. The dynamic peak strain and average strain rate showed a quadratic function with the water bath temperature. The dynamic peak strain before 45°C decreased with the temperature increasing, and the dynamic peak strain after 45°C increased with the temperature increasing. The dynamic elastic modulus increased first and then decreased with the increase of water bath temperature and reached the maximum at 45°C. The failure pattern of sandstone is spalling. With the increase of water bath temperature, the fracture degree of the specimen gradually decreases.